Intracellular C4BPA Levels Regulate NF-κB-Dependent Apoptosis - Monica M. Olcina; Ryan K. Kim; Nikolas G. Balanis; Caiyun Grace Li; Rie von Eyben; Thomas G. Graeber; Daniel Ricklin; Manuel Stucki; Amato J. Giaccia (iScience, 2020)
Summary: The importance of innate immunity in cancer is increasingly being recognized with recent reports suggesting tumor cell-intrinsic intracellular functions for innate immunity proteins. However, such functions are often poorly understood, and it is unclear whether these are affected by patient-specific mutations. Here, we show that C4b-binding protein alpha chain (C4BPA), typically thought to reside in the extracellular space, is expressed intracellularly in cancer cells, where it interacts with the NF-κB family member RelA and regulates apoptosis. Interestingly, intracellular C4BPA expression is regulated in a stress- and mutation-dependent manner and C4BPA mutations are associated with improved cancer survival outcome. Using cell lines harboring patient-specific C4BPA mutations, we show that increasing intracellular C4BPA levels correlate with sensitivity to oxaliplatin-induced apoptosis in vitro and in vivo. Mechanistically, sensitive C4BPA mutants display increased IκBα expression and increased inhibitory IκBα-RelA complex stability. These data suggest a non-canonical intracellular role for C4BPA in regulating NF-κB-dependent apoptosis.